Pleiotrophin as a central nervous system neuromodulator, evidences from the hippocampus - González-Castillo, Celia; Ortuño-Sahagún, Daniel; Guzmán-Brambila, Carolina; Pallàs, Mercè; Rojas-Mayorquín, Argelia Esperanza (Frontiers in Cellular Neuroscience, 2015)
Pleiotrophin (PTN) is a secreted growth factor, and also a cytokine, associated with the extracellular matrix, which has recently starting to attract attention as a significant neuromodulator with multiple neuronal functions during development. PTN is expressed in several tissues, where its signals are generally related with cell proliferation, growth, and differentiation by acting through different receptors. In Central Nervous System (CNS), PTN exerts post-developmental neurotrophic and -protective effects, and additionally has been involved in neurodegenerative diseases and neural disorders. Studies in Drosophila shed light on some aspects of the different levels of regulatory control of PTN invertebrate homologs. Specifically in hippocampus, recent evidence from PTN Knock-out (KO) mice involves PTN functioning in learning and memory. In this paper, we summarize, discuss, and contrast the most recent advances and results that lead to proposing a PTN as a neuromodulatory molecule in the CNS, particularly in hippocampus.